The Development of Natural Laboratory with Mangroves Ecotourism Concept for Geography Learning in Senior High School in the Olaya Village, Parigi Moutong Regency - Maliki, Rendra Zainal (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The development of this natural laboratory is motivated due to there is no development for learning in schools. The potential of mangroves forest area in the Olaya Village are wide enough so that it can be used as a natural laboratory. The reason chosen Olaya village is as seen from some aspects of the assessment parameters such as mangroves forest wide, the distance of the settlement, the condition of naturally mangroves forest, access to the location and condition of the communities who support it. The development of natural laboratory is aim to be able to facilitate student in learning where student are provided differentiated learning that is direct observing the object being studied. The concept of ecotourism mangroves are used as a natural laboratory support due to in the Olaya Village has an excellent mangroves and the role of local communities are able to maintain mangroves. The plan in the development of this natural laboratory will provide benefits both for student in the learning process and for the local communities in developing the potential of the region. The development of this natural laboratory combines two concepts that are education and tourism.